Novel bioactive parathyroid hormone and related peptides in teleost fish - Canario, Adelino V. M. (2014)
We report the identification, gene expression and biological activity of two parathyroid hormones (PTH; PTHA and PTHB), two PTH-related peptides (PTHrP; PTHrPA and PTHrPB) and a PTH-like ligand (PTH-L) with hybrid characteristics in puffer fishes (Takifugu rubripes and Tetraodon fluviatilis). Experimental data are consistent with PTH-L and PTHrPA having calciotropic activities equivalent, respectively, to tetrapod PTH and PTHrP. We hypothesise on the basis of phylogenetic and functional analysis that PTH-L could be a fish relic of an ancestral PTH/PTHrP gene.